x^2-25y^2-6x-9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=\left(x^2y+3\right)^2\\ b,=\left(2x+y\right)^2\\ c,=\left(5y^2-1\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2+2x+1=\left(x+1\right)^2\)
b) \(x^2+8x+16=\left(x+4\right)^2\)
c) \(x^2+6x+9=\left(x+3\right)^2\)
d) \(4x^2+4x+1=\left(2x+1\right)^2\)
e) \(36+x^2-12x=x^2-12x+36=\left(x-6\right)^2\)
f) \(4x^2+12x+9=\left(2x+3\right)^2\)
g) \(x^4+81+18x^2=x^4+18x^2+81=\left(x^2+9\right)^2\)
h) \(9x^2+30xy+25y^2=\left(3x+5y\right)^2\)
a, \(x^2\) + 2\(x\) + 1 = (\(x\) + 1)2
b, \(x^2\) + 8\(x\) + 16 = (\(x\) + 4)2
c, \(x^2\) + 6\(x\) + 9 = (\(x\) + 3)2
d, 4\(x^2\) + 4\(x\) + 1 = (2\(x\) + 1)2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(5x\left(x-9\right)-x+9\)
\(=5x\left(x-9\right)-\left(x-9\right)\)
\(=\left(x-9\right)\left(5x-1\right)\)
b) Ta có: \(6x^2+7x-3\)
\(=6x^2+9x-2x-3\)
\(=3x\left(2x-3\right)-\left(2x-3\right)\)
\(=\left(2x-3\right)\left(3x-1\right)\)
d) Ta có: \(x^2-10xy+25y^2\)
\(=x^2-2\cdot x\cdot5y+\left(5y\right)^2\)
\(=\left(x-5y\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
c: \(x^2-4x^2y^2+y^2+2xy\)
\(=\left(x+y\right)^2-\left(2xy\right)^2\)
\(=\left(x+y+2xy\right)\left(x+y-2xy\right)\)
d: \(7x^2-14xy^2+7y^4\)
\(=7\left(x^2-2xy^2+y^4\right)\)
\(=7\left(x-y^2\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\text{a) }-x^2+10x-25\\ =-\left(x^2-10x+25\right)\\ =-\left(x-5\right)^2\)
\(\text{b) }-x^2-6x-9\\ =-\left(x^2+6x+9\right)\\ =-\left(x+3\right)^2\)
\(\text{c) }-4x^2+20xy-25y^2\\ =-\left(4x^2-20xy+25y^2\right)\\ =-\left(2x-5y\right)^2\)
\(d\text{) }!!!\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 9x2 - 36
=(3x)2-62
=(3x-6)(3x+6)
=4(x-3)(x+3)
b) 2x3y-4x2y2+2xy3
=2xy(x2-2xy+y2)
=2xy(x-y)2
c) ab - b2-a+b
=ab-a-b2+b
=(ab-a)-(b2-b)
=a(b-1)-b(b-1)
=(b-1)(a-b)
P/s đùng để ý đến câu trả lời của mình
Sửa đề
x² - 25y² - 6x + 9
= (x² - 6x + 9) - 25y²
= (x - 3)² - (5y)²
= (x - 3 - 5y)(x - 3 + 5y)
= (x - 5y - 3)(x + 5y - 3)